The discovery of pasta : a history in ten dishes - Cesari, Luca (Pegasus Books, Ltd., 2023)
"In this hugely charming and entertaining chronicle of everyone's favorite dish, acclaimed Italian food writer and historian Luca Cesari draws on literature, history, and many classic recipes in order to enlighten pasta lovers everywhere, both the gourmet and the gluten free. What is Italy without pasta? Come to think of it, where would the rest of us be without this staple of global cuisine? The wheat-based dough first appeared in the Mediterranean in ancient times. Yet despite these remote beginnings, pasta wasn't wedded to sauce until the nineteenth century. Once a special treat, it has been served everywhere from peasant homes to rustic taverns to royal tables, and its surprising past holds a mirror up to the changing fortunes of its makers. Full of mouthwatering recipes and outlandish anecdotes--from (literal) off-the-wall 1880s cooking techniques to spaghetti conveyer belts in 1940 and the international amatriciana scandal in 2021--Luca Cesari embarks on a tantalizing and edifying journey through time to detangle the heritage of this culinary classic."--